Diverse CRISPR-Cas responses and dramatic cellular DNA changes and cell death in pKEF9-conjugated Sulfolobus species - Liu, Guannan (Nucleic Acids Res, 2016)
The Sulfolobales host a unique family of crenarchaeal conjugative plasmids some of which undergo complex rearrangements intracellularly. Here we examined the conjugation cycle of pKEF9 in the recipient strain Sulfolobus islandicus REY15A. The plasmid conjugated and replicated rapidly generating high average copy numbers which led to strong growth retardation that was coincident with activation of CRISPR-Cas adaptation. Simultaneously, intracellular DNA was extensively degraded and this also occurred in a conjugated Δcas6 mutant lacking a CRISPR-Cas immune response. Furthermore, the integrated forms of pKEF9 in the donor Sulfolobus solfataricus P1 and recipient host were specifically corrupted by transposable orfB elements, indicative of a dual mechanism for inactivating free and integrated forms of the plasmid. In addition, the CRISPR locus of pKEF9 was progressively deleted when conjugated into the recipient strain. Factors influencing activation of CRISPR-Cas adaptation in the recipient strain are considered, including the first evidence for a possible priming effect in Sulfolobus. The 3-Mbp genome sequence of the donor P1 strain is presented.